Ochlochaete incrustans sp. nov., a new species of freshwater ulvophycean algae from California, USA, with notes on Friedaea torrenticola. Issue 4 (1st July 2018) - Hall, John D.; Sheath, Robert G.; McCourt, Richard M.; Stancheva, Rosalina
Abstract: During a broad survey of the stream algae of California, a rare and unusual green alga was encountered. Samples were collected in three sites, one 200 m from a stream outlet into the Pacific Ocean and the others 6–20 km inland from the ocean. We initially identified the alga as Friedaea torrenticola Schmidle, which had been previously reported from California by G.M. Smith in 1933. However, additional observations and analysis led us to conclude that the specimen represented a new species of the primarily marine genus Ochlochaete. Ochlochaete incrustans sp. nov . grows in dense, lime-encrusted mats in fast-flowing streams. The thallus is a branched filament terminating in slightly clavate cells. Some intercalary cells are furnished with long, colourless setae. Transmission electron microscopic analysis revealed that the pyrenoid is traversed by a single, straight thylakoid similar to the ulvophycean alga Phaeophila . Molecular phylogenetic analysis of the new species based on the nuclear-encoded 18S rDNA and chloroplast-encoded tufA gene sequences revealed that it is most closely related to Ochlochaete hystrix Thwaites (Ulvaceae, Ulvophyceae).